Positive electrode material and battery

By controlling the proportion of particles less than 1 μm in the positive electrode material and the surface enrichment of sulfur elements, the problem of poor structural stability of the positive electrode material is solved, and the circulation performance is significantly improved.

CN119725485APending Publication Date: 2025-03-28SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411962899.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing positive electrode materials have poor structural stability during circulation, resulting in a degradation of circulation performance.

Method used

By controlling the proportion of the number of particles with particle size less than 1 μm in the positive electrode material to be 6% to 18%, and the surface enrichment of sulfur elements is limited to ≤70%, so as to reduce side reactions with the electrolyte and inhibit structural damage.

Benefits of technology

The cycle stability and structural stability of the positive electrode material are improved and the cycle performance is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725485A_ABST
    Figure CN119725485A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a battery. The surface enrichment degree beta of the sulfur element in the positive electrode material is equal to A2 / A1, beta is less than or equal to 70%, A1 is the total mass content of the sulfur element in the positive electrode material, and A2 is the mass content of the sulfur element in free sulfate radicals of the positive electrode material; in a scanning electron microscope (SEM) pattern of the positive electrode material, the proportion of the number of particles with the particle size smaller than 1 micron in the positive electrode material is 6%-18%. According to the positive electrode material, lattice rotation of the positive electrode material can be reduced, so that the structural stability and the cycle performance of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials, and in particular relates to positive electrode materials and batteries. Background Art

[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their high energy density, good safety performance, long cycle life and environmental friendliness. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). Therefore, researchers currently focus on developing large-capacity and high-voltage positive electrode materials to improve the energy density of lithium-ion batteries. Positive electrode materials are the core components in battery development. However, as the capacity of positive electrode materials increases, it also brings problems such as reduced cycle and poor structural stability.

[0003] Therefore, how to improve the cycle structural stability of positive electrode materials is still an urgent problem that needs to be solved. Summary of the invention

[0004] The present application provides a positive electrode material and a battery. The positive electrode material of the present application can reduce the lattice rotation of the positive electrode material, thereby improving the structural stability and cycle performance of the positive electrode material.

[0005] In a first aspect, the present application provides a positive electrode material, wherein the surface enrichment of sulfur in the positive electrode material is β=A2 / A1, β≤70%, A1 is the total mass content of sulfur in the positive electrode material, and A2 is the mass content of sulfur in free sulfate ions in the positive electrode material;

[0006] In a scanning electron microscope (SEM) image of the positive electrode material, the number of particles with a particle size less than 1 μm in the positive electrode material accounts for 6% to 18%.

[0007] In some embodiments, the chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, wherein 0.98≤x≤1.1, 0.5≤a≤0.98, 0<b≤0.2, 0<c≤0.30, 0≤d≤0.1, a+b+c+d=1, the N element includes at least one of Mn and Al, and the M1 element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.

[0008] In some embodiments, the total mass content A1 of sulfur element in the positive electrode material satisfies 50ppm≤A1≤1000ppm.

[0009] In some embodiments, the mass content A2 of sulfur element in the surface free sulfate in the positive electrode material satisfies 0ppm<A2≤700ppm. In some embodiments, the positive electrode material includes primary particles and a coating layer located on at least a portion of the surface of the primary particles, the coating layer includes element M2, and the element M2 includes at least one of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co and Mn.

[0010] In some embodiments, the cathode material is a single crystal cathode material.

[0011] In some embodiments, the median particle size of the positive electrode material is 1.5 μm to 5.0 μm.

[0012] In some embodiments, the initial internal resistance of the positive electrode material is 30Ω or less.

[0013] In some embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g~1.2m 2 / g.

[0014] In some embodiments, the compaction density of the positive electrode material is 3.0 g / cm 3 ~3.3g / cm 3 .

[0015] In some embodiments, during the first cycle of charge and discharge, the structural recovery degree δ of the positive electrode material satisfies: 99.7%≤δ≤100.0%; wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first cycle of discharge.

[0016] In a third aspect, the present application provides a battery, comprising a positive electrode material.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The positive electrode material provided in the present application reduces the side reaction between the positive electrode material and the electrolyte by controlling the number of particles with a particle size of less than 1 μm in the positive electrode material to account for 6% to 18%, thereby improving the cycle stability of the positive electrode material. The present application further suppresses the structural damage of the positive electrode material caused by the side reaction by controlling the surface enrichment of sulfur element in the positive electrode material to ≤70%, thereby further improving the structural stability and long cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0021] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0022] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0023] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0024] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.

[0025] The present application provides a positive electrode material; the surface enrichment of sulfur in the positive electrode material is β=A2 / A1, β≤70%, A1 is the total mass content of sulfur in the positive electrode material, and A2 is the mass content of sulfur in free sulfate ions in the positive electrode material;

[0026] In a scanning electron microscope (SEM) image of the positive electrode material, the number of particles with a particle size less than 1 μm in the positive electrode material accounts for 6% to 18%.

[0027] Due to the extremely high reactivity of particles below 1 μm, the positive electrode material provided in the present application reduces the side reaction of the positive electrode material with the electrolyte by controlling the number of particles with a particle size of less than 1 μm in the positive electrode material to account for 6% to 18%, thereby improving the cycle stability of the positive electrode material. The present application further suppresses the structural damage of the positive electrode material caused by the side reaction by controlling the surface enrichment of sulfur in the positive electrode material to ≤70%, thereby further improving the structural stability and long cycle performance of the positive electrode material. It should be noted that the ratio of A1 to A2 can characterize the enrichment of sulfur on the surface of the positive electrode material. The larger the ratio of A1 to A2, the higher the sulfur content on the surface of the positive electrode material, and the sulfur is enriched on the surface of the positive electrode material; the smaller the ratio of A1 to A2, the lower the sulfur content on the surface of the positive electrode material, and the higher the sulfur in the bulk phase. Wherein, A1 is the total mass content of sulfur in the positive electrode material, and A2 is the mass content of sulfur in the free sulfate ions of the positive electrode material. The inventor speculates that this is because some sulfur atoms are doped into the lattice of the positive electrode material and replace the oxygen atoms in the layered structure of the positive electrode material. The appropriate amount of sulfur atom doping can increase the migration rate of lithium ions, inhibit heterogeneous reactions, reduce the lattice rotation of the positive electrode material, and improve the structural stability of the positive electrode material. At the same time, after some sulfur atoms are doped into the lattice, they can be connected to the oxygen atoms in the lattice through transition metal atoms (such as Ni, Co, Mn, etc.), and form chemical bonds with stronger bond energy, which can enhance the tolerance of the positive electrode material to lattice deformation, alleviate the generation of cracks and irreversible phase changes inside the positive electrode material particles, and improve the cycle stability of the positive electrode material. In this application, while controlling the doping of sulfur elements, the number of particles less than 1 μm is controlled, which can reduce the side reactions of the positive electrode material and the electrolyte, improve the cycle performance of the positive electrode material, and at the same time, the doping of sulfur atoms can inhibit the lattice rotation of the positive electrode material, improve the structural stability of the positive electrode material, and further reduce the structural damage caused by the side reactions of the positive electrode material; under the synergistic effect of the two, the positive electrode material can have excellent structural stability and long cycle performance.

[0028] It should be noted that the mass content of sulfur in the free sulfate ions of the positive electrode material is A2. It should be noted that the mass proportion of sulfur in sulfate is 1 / 3. In this application, 0.5 g of sample was weighed and dissolved in 50 ml of water. After ultrasonic filtration for 5 min, the free SO4 in the filtrate was measured by ion chromatography. 2- The mass content of the ion is a2. The total mass content A1 of sulfur in the positive electrode material is tested by inductively coupled plasma optical emission spectrometry. Specifically, 0.3 g of the sample is digested with aqua regia, cooled and fixed to volume, and then the total mass content A1 of the S element is tested by inductively coupled plasma optical emission spectrometry (Agilent 5110 ICP-OES).

[0029] In some embodiments, the total mass content of sulfur in the positive electrode material is A1, 50ppm≤A1≤1000ppm; specifically, it can be 50ppm, 70ppm, 100ppm, 150ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm or 1000ppm, etc., and of course, it can also be other values ​​within the above range, which are not limited here. The presence of an appropriate amount of S element in the positive electrode material can increase the migration rate of lithium ions, inhibit heterogeneous reactions, reduce the lattice rotation of the positive electrode material, and enhance the structural stability of the positive electrode material. When the total mass content of sulfur in the positive electrode material is too high, the capacity of the positive electrode material decreases. When the total mass content of sulfur in the positive electrode material is too low, it is difficult to inhibit the lattice rotation of the positive electrode material. Preferably, 300ppm≤A1≤800ppm.

[0030] In some embodiments, the mass content A2 of sulfur element in the surface free sulfate in the positive electrode material satisfies 0ppm<A2≤700ppm. Specifically, it can be 50ppm, 70ppm, 100ppm, 150ppm, 500ppm, 600ppm or 700ppm, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0031] In some embodiments, the surface enrichment of sulfur in the positive electrode material is β, which can be 70%, 65%, 60%, 50%, 45%, 40%, 30%, 25%, 20% or 10%, etc., and of course it can also be other values ​​within the above range, which are not limited here. The presence of an appropriate amount of S element doping in the positive electrode material can increase the migration rate of lithium ions, inhibit heterogeneous reactions, reduce the lattice rotation of the positive electrode material, and enhance the structural stability of the positive electrode material. The higher the surface enrichment, the less sulfur atoms are doped into the crystal structure of the positive electrode material, and the inhibitory effect on the lattice rotation of the positive electrode material decreases. Preferably, the surface enrichment of sulfur in the positive electrode material is 40%≤β≤50%.

[0032] In some embodiments, the positive electrode material has the general chemical formula Li x Ni a Co b N c M1 d O2, wherein 0.98≤x≤1.1, 0.5≤a≤0.98, 0<b≤0.2, 0<c≤0.30, 0≤d≤0.1, a+b+c+d=1, the N element includes at least one of Mn and Al, and the M1 element is a metal element.

[0033] Specifically, the value of x can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the value of a can be 0.5, 0.6, 0.7, 0.8, 0.82, 0.84, 0.85, 0.88, 0.89, 0.90, 0.92, 0.95 or 0.98, and the value of b can be 0.001, 0.01, 0.05, 0. 1, 0.15, 0.16, 0.17, 0.19 or 0.2, etc., the value of c can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.18, 0.2, 0.25 or 0.3, etc., the value of d can be 0, 0.001, 0.005, 0.006, 0.008, 0.009, 0.01, 0.02, 0.03, 0.05, 0.07 or 0.1, etc., and is not limited here.

[0034] In some embodiments, the M1 element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y. It can be understood that an appropriate amount of M1 element doping can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing.

[0035] In some embodiments, in the scanning electron microscope image (SEM) of the positive electrode material, the number of particles with a particle size less than 1 μm may specifically account for 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16% or 18%, etc., and of course, it may also be other values ​​within the above range, which are not limited here. When the number of particles with a particle size less than 1 μm accounts for too much, it means that the number of micropowders increases, the particle size distribution width of the positive electrode material increases, and the compaction density of the positive electrode material can be increased, but the increase in the number of micropowders will lead to an increase in the specific surface area of ​​the positive electrode material, causing an increase in the side reactions between the positive electrode material and the electrolyte, and reducing the structural stability and cycle stability of the positive electrode material. When the number of particles with a particle size less than 1 μm accounts for too little, the transmission path of lithium ions increases, the initial DCR of the positive electrode material increases, and the compaction density of the positive electrode material decreases. The present application controls the proportion of particles with a particle size less than 1 μm within the above range, which can ensure that the compaction density of the positive electrode material is within an appropriate range, improve the energy density of the positive electrode material, and at the same time help reduce the occurrence of side reactions between the positive electrode material and the electrolyte, and improve the structural stability and cycle stability of the positive electrode material.

[0036] In some embodiments, the positive electrode material includes primary particles and a coating layer located on at least a portion of the surface of the primary particles, the coating layer includes an oxide of element M2 and / or a lithium ion conductor of element M2, and the element M2 includes at least one of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co and Mn. The presence of the coating layer on the surface of the primary particles can reduce the occurrence of side reactions between the primary particles and the electrolyte and improve the structural stability of the primary particles.

[0037] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nano-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color within a grain is the same, so as to judge that the orientation of at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0038] It can be understood that the above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particles" refer to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particles" refer to secondary particles formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1um and 5um. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional polycrystalline "secondary particles".

[0039] It should be specifically pointed out that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal morphology-like" positive electrode materials, which only show large single crystal-like particle sizes in size, as distinguished from polycrystals composed of many small primary particles.

[0040] In some embodiments, the median particle size of the positive electrode material is 1.5 μm to 5.0 μm, specifically 1.0 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm or 5.0 μm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Since most of the particles in the positive electrode material are primary particles, that is, the median particle size of the primary particles is within the above range, the primary particles within this size range can effectively control the diffusion pathway of lithium ions, have better electrochemical properties, and have higher discharge capacity and excellent rate performance.

[0041] In some embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g~1.2m 2 / g; specifically, it can be 0.50m 2 / g, 0.55m 2 / g, 0.58m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.8m 2 / g, 0.85m 2 / g, 0.9m 2 / g, 0.95m 2 / g, 1.0m 2 / g, 1.05m 2 / g, 1.1m 2 / g or 1.2m 2 / g, etc., and of course, other values ​​within the above range may also be possible, which are not limited here. Controlling the specific surface area of ​​the positive electrode material within the above range can effectively control the side reaction between the positive electrode material and the electrolyte, and improve the capacity of the positive electrode material.

[0042] In some embodiments, the powder compaction density of the positive electrode material is 3.0 g / cm 3 ~3.3g / cm 3 , specifically 3.0g / cm 3、3.05g / cm 3 、3.1g / cm 3 、3.15g / cm 3 、3.2g / cm 3 , 3.25g / cm 3 or 3.3 g / cm 3 The density of the cathode material powder is controlled within the above range, which is beneficial to improving the specific capacity of the cathode material and the energy density of the battery made of the cathode material.

[0043] In some embodiments, during the first cycle of charge and discharge, the structural recovery degree δ of the positive electrode material satisfies: 100.00% ≥ δ ≥ 99.70%; wherein δ = θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first cycle of discharge.

[0044] Specifically, δ can be 99.7%, 99.8%, 99.85%, 99.9%, 99.95% or 100.00%, etc., and of course, it can also be other values ​​within the above range, which is not limited here. It can be understood that the degree of structural recovery of the positive electrode material is controlled within the above range. It can be seen that during the charge and discharge cycle, the crystal structure of the positive electrode material can remain stable, the irreversible phase change of the positive electrode material is reduced, and the lattice structure attenuation is greatly improved, which is conducive to maintaining the cycle structure stability of the positive electrode material.

[0045] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0046] S10, nickel, cobalt and salt solution containing N element are prepared into a mixed solution according to a certain stoichiometric ratio, and an appropriate amount of dilute sulfuric acid solution is added, and atomized by a plasma rotating electrode to form micronized droplets with a particle size of 2μm to 200μm, and then the droplets are passed into a roasting furnace for thermal decomposition to prepare an oxide precursor; wherein, based on the total molar content of metal Ni+Co+N being 100%, the amount of H2SO4 added is 0.015% to 0.3%. Wherein, the N element includes at least one of Mn and Al.

[0047] S20, subjecting the mixture of the oxide precursor and the lithium source to a sintering treatment, and crushing the primary sintering product to obtain a positive electrode material, wherein the primary sintering treatment includes sequentially performing a first heating stage, a second heating stage, a first cooling stage and a third heating stage, the temperature of the first heating stage is 300°C to 600°C, the temperature of the second heating stage is 720°C to 1000°C, the temperature of the first cooling stage is 500°C to 700°C, and the temperature of the third heating stage is 720°C to 1000°C.

[0048] In the preparation method of the positive electrode material provided in the present application, during the preparation process of the oxide precursor, an appropriate amount of dilute sulfuric acid is added to achieve doping of the oxide precursor, and the oxide precursor containing sulfate ions is subjected to a primary sintering treatment. During the primary sintering process, part of the sulfate ions doped into the precursor can form OT with metal elements and oxygen elements. M -S chemical bond, T M As a transition metal in the lattice, this chemical bond has stronger bond energy, which can enhance the tolerance of the positive electrode material to lattice deformation, significantly alleviate the generation of cracks inside the positive electrode material particles and irreversible phase changes, and improve the cycle stability of the positive electrode material.

[0049] The preparation method of the present application is described in detail below with reference to the examples:

[0050] Step S10, prepare nickel, cobalt and salt solution containing N element into a mixed solution according to a certain stoichiometric ratio, add an appropriate amount of dilute sulfuric acid solution, and atomize through a plasma rotating electrode to form micronized droplets with a particle size of 2μm to 200μm, and then pass the droplets into a calcining furnace for thermal decomposition to prepare an oxide precursor.

[0051] In some embodiments, the stoichiometric ratio range between nickel, cobalt and N elements meets the following conditions: 0.5≤Ni<1, 0<Co≤0.2, 0<N≤0.35; the molar ratio of Ni:Co:N can be specifically 0.60:0.05:0.35, 0.67:0.05:0.28, 0.90:0.5:0.05 or 0.98:0.01:0.01, etc.

[0052] In some embodiments, the salt solution is at least one of nitrate, hydrochloride, carbonate, oxalate, and acetate. For example, the nickel salt solution can be at least one of nickel chloride, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate. Of course, nickel, manganese, and N elements can also be recycled materials of ternary positive electrode materials, which are not limited here.

[0053] In some embodiments, based on the total molar content of metal Ni, Co, and N as 100%, the amount of H2SO4 added is 0.015% to 0.3%. Specifically, the amount of H2SO4 added can be 0.015%, 0.03%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.3%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0054] In some embodiments, the calcining furnace includes a first temperature zone, a second temperature zone, and a third temperature zone. The temperature of the first temperature zone is 300°C to 500°C, and the droplets are rapidly dehydrated at this stage. The temperature of the second temperature zone is 1000°C to 1200°C, and the material residence time is 2s to 10s. The short high temperature can promote the doping of sulfur elements to the precursor, and can effectively prevent the precursor particles from growing too large and affecting the reaction activity of the precursor. The third temperature zone is 500°C to 800°C. The material in the third temperature zone undergoes thermal decomposition, and various metal salts decompose to form oxide precursor particles.

[0055] In some embodiments, the oxygen volume concentration in the roasting furnace is controlled to be ≤21%.

[0056] In some embodiments, the temperature of the first temperature zone can be 300°C, 350°C, 380°C, 400°C, 430°C, 450°C or 500°C, etc., and of course it can also be other values ​​within the above range, which is not limited here. The residence time in the first temperature zone is 1 min to 5 min, and can be 1 min, 2 min, 3 min, 4 min or 5 min, etc., and of course it can also be other values ​​within the above range.

[0057] In some embodiments, the temperature of the second temperature may be 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, etc., and of course it may also be other values ​​within the above range, which is not limited here. The residence time in the second temperature zone is 2s to 10s, and may be 2s, 3s, 5s or 10s, etc., and of course it may also be other values ​​within the above range.

[0058] In some embodiments, the temperature of the third temperature zone can be 510°C, 520°C, 530°C, 550°C, 600°C, 650°C, 680°C, 700°C, 750°C or 800°C, etc., and of course it can also be other values ​​within the above range, which is not limited here. The residence time in the third temperature zone is 3min to 8min, and can be 3min, 4min, 5min, 6min or 8min, etc., and of course it can also be other values ​​within the above range.

[0059] In some embodiments, the calcined product is subjected to airflow pulverization to control the oxide precursor D50 to be 2.5 μm to 4.5 μm, and Dmax < 20 μm. Specifically, D50 may be 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.2 μm or 4.5 μm, etc., and may also be other values ​​within the above range.

[0060] The present application controls the particle size distribution of the precursor by airflow pulverizing the calcined product, which is beneficial for controlling the number ratio and electrochemical performance of particles with too small a particle size of the positive electrode material.

[0061] In some embodiments, a compound containing element M1 is further added to the mixed solution according to a target doping ratio, which may specifically be a nitrate containing element M1, a hydrochloride containing element M1, an acid containing element M1, etc., which is not limited here.

[0062] In some embodiments, the M1 element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn, and Y.

[0063] In some embodiments, the oxide precursor has a general chemical formula of Ni x Co y N z M1 d O e , wherein 0.50≤x≤0.98, 0<y≤0.20, 0<z≤0.35, 0≤d≤0.1, x+y+z+d=1; 1≤e≤1.5. wherein the N element is Mn or Al.

[0064] S20, performing a primary sintering treatment on the mixture of the oxide precursor and the lithium source, and crushing the primary sintering product to obtain a positive electrode material.

[0065] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium sulfate and lithium oxalate. Preferably, the lithium salt is lithium carbonate.

[0066] In some embodiments, the amount of the lithium source and the oxide precursor added satisfies: the ratio of the molar amount of Li to the total molar amount of all metals in the oxide precursor is (0.98-1.1):1, specifically 0.98:1, 1.02:1, 1.05:1, 1.1:1, etc., and of course other values ​​within the above range are also possible, which are not limited here. Within this range, the degree of Li / Ni cation mixing can be reduced, and the excessive residual lithium on the surface of the sintered product can be prevented from affecting the processing performance and safety performance.

[0067] In some embodiments, the mixing conditions for obtaining the mixture are: solid phase mixing at 10° C. to 50° C. for 0.3 h to 3 h.

[0068] In some embodiments, the temperature of solid-phase mixing can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, and the time of solid-phase mixing can be 0.3h, 0.4h, 0.5h, 0.6h, 0.8h, 1h, 1.5h, 1.8h, 2.5h or 3h, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0069] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, and a VC mixer.

[0070] In some embodiments, the primary sintering process includes sequentially performing a first heating stage, a second heating stage, a first cooling stage and a third heating stage, the temperature of the first heating stage is 300°C to 600°C, the temperature of the second heating stage is 720°C to 1000°C, the temperature of the first cooling stage is 500°C to 700°C, and the temperature of the third heating stage is 720°C to 1000°C.

[0071] In some embodiments, the temperature of the first heating stage can be 300°C, 350°C, 380°C, 400°C, 430°C, 450°C, 500°C, 550°C, 580°C or 600°C, etc. The time of the first heating stage is 3h to 5h, and can be 3h, 3.5h, 4h, 4.5h or 5h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The temperature of the first heating stage is relatively low, and the lithium source can be fully melted and react with the oxide precursor.

[0072] In some embodiments, the heating rate in the first heating stage is 15°C / min to 20°C / min, specifically 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0073] In some embodiments, the temperature of the second heating stage can be 720°C, 770°C, 800°C, 880°C, 900°C or 1000°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The time of the second heating stage is 4h to 12h, and can be 4h, 5h, 6h, 8h, 9h, 10h, 11h or 12h, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The crystals of the positive electrode material are fully grown in the second heating stage.

[0074] In some embodiments, the heating rate in the second heating stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0075] In some embodiments, the temperature of the first cooling stage can be 500°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 690°C or 700°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The time of the first cooling stage is 2h to 6h, and can be 2h, 3h, 4h, 5h, 5.5h or 6h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Through the cooling treatment, the lattice stress of the positive electrode material can be released and the stability of the crystal can be improved.

[0076] In some embodiments, the cooling rate in the first cooling stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0077] In some embodiments, the temperature of the third heating stage can be 720°C, 770°C, 800°C, 880°C, 900°C or 1000°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The time of the third heating stage is 1h to 3h, and can be 1h, 1.5h, 2h, 2.5h or 3h, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The crystals of the positive electrode material are fully grown in the third heating stage.

[0078] In some embodiments, the heating rate in the third heating stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0079] In some embodiments, the sintered product is cooled to room temperature after the third temperature rising stage.

[0080] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 95%.

[0081] In the present application, the temperature at each stage of a sintering process is adjusted according to the molar content in the oxide precursor. The higher the Ni content, the lower the sintering temperature, thereby effectively improving the lithium-nickel mixing phenomenon.

[0082] In some embodiments, the method further comprises: mixing the crushed product with a coating agent containing metal M2, and then performing a secondary sintering process to obtain a positive electrode material.

[0083] In some embodiments, the crushing method includes at least one of a double roller, a plowshare mixer / crusher, and a jet mill.

[0084] In some embodiments, the coating agent containing metal M2, M2 is selected from at least one of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co and Mn. The coating agent containing metal M2 can be a salt or oxide of metal M. Preferably, the coating agent containing metal M2 includes a Nb compound and / or a W compound.

[0085] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 95%.

[0086] In some embodiments, the temperature of the secondary sintering treatment is 300°C to 800°C, specifically 300°C, 320°C, 330°C, 350°C, 380°C, 400°C, 450°C, 500°C, 550°C, 650°C, 700°C or 800°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] In some embodiments, the holding time of the secondary sintering treatment is 6h to 24h, specifically 6h, 8h, 10h, 12h, 15h, 18h or 24h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.

[0089] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.

[0090] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.

[0091] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.

[0092] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0093] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .

[0094] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.

[0095] In some embodiments, the preparation method of the positive electrode sheet 1 is: the positive electrode active material, the conductive agent, the binder and the solvent are mixed uniformly in a certain proportion to form a slurry, and then the slurry is uniformly coated on the positive electrode collector 11, and vacuum dried at a certain temperature to obtain the positive electrode sheet 1.

[0096] In some embodiments, the conductive agent includes at least one of conductive carbon black, graphene, carbon nanofiber, Ketjen black, graphite, acetylene black, and MXene.

[0097] In some embodiments, the binder includes at least one of sodium carboxymethyl cellulose, cyclodextrin, styrene rubber latex, polyacrylate, and polyvinylidene fluoride.

[0098] In some embodiments, the solvent is selected from at least one of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide.

[0099] In some embodiments, the vacuum drying temperature is 60°C to 120°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the vacuum drying temperature is 110°C.

[0100] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.

[0101] In some embodiments, the negative electrode current collector 21 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to at least one of natural graphite negative electrode material, natural graphite negative electrode material or silicon-based negative electrode material.

[0102] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0103] Test method:

[0104] (1) Test of free sulfate in cathode materials

[0105] Weigh 0.5 g of sample and dissolve it in 50 ml of water. After filtration under ultrasonic for 5 min, measure the free SO4 in the filtrate using ion chromatography (instrument: Thermo Fisher ion chromatograph ICS6000 HPIC). 2- The mass content of the ion is a2.

[0106] Since the mass content of sulfur in sulfate ions is 1 / 3, the mass content of sulfur in the free sulfate ions of the positive electrode material is A2=a2 / 3.

[0107] (2) Test of the total mass content of sulfur in the positive electrode material

[0108] Take 0.3 g of sample and add aqua regia for digestion. After cooling and constant volume, the total mass content A1 of S element is tested by inductively coupled plasma optical emission spectrometer (Agilent 5110 ICP-OES).

[0109] The surface enrichment of sulfur element β = A2 / A1. The ratio of A1 to A2 can characterize the enrichment of sulfur element on the surface of the positive electrode material. The larger the ratio of A1 to A2, the higher the sulfur content on the surface of the positive electrode material, and the sulfur element is enriched on the surface of the positive electrode material; the smaller the ratio of A1 to A2, the lower the sulfur content on the surface of the positive electrode material, and the higher the sulfur element in the bulk phase.

[0110] (3) The proportion of particles with a particle size less than 1 μm in the positive electrode material

[0111] 1) Use a cotton swab to pick up a small amount of powder sample and apply it evenly and densely on the conductive glue; use a hair dryer to slowly blow in the direction where there are no other samples, and when it is confirmed to be evenly applied on the surface, blow strongly for more than 10 times until there is no residual powder;

[0112] 2) Set the basic conditions of SEM: voltage 5 kV, current 12 mA, magnification 2k, contrast and brightness are adjusted using the auto key, and the measurement position is set to the part with 300 to 800 particles (center value 500);

[0113] 3) Save the SEM image. Each sample is measured under this condition for 10 photos. All the pictures are imported into the software through Metis Vision software for manual identification. The bottom edge size and border size of the identification are adjusted according to the specific SEM image. The particles with a size range of dmin-dmax, an aspect ratio of 0-9.0, and an area ratio of 0-1.00 are identified.

[0114] 4) Calculate the percentage of particles with a diameter less than 1 μm based on the measured particle size.

[0115] (4) IPC test method for positive electrode materials:

[0116] Equipment: Agilent 5110ICP-OES plasma inductively coupled electrochemical analyzer.

[0117] Method: Take 0.3g sample and add aqua regia for digestion. After cooling and constant volume, take 1mL and dilute 100 times to test the main elements Li / Ni / Co / Mn, and the mother liquor is used to test the impurity elements.

[0118] (5) XRD test method of positive electrode material:

[0119] Equipment: XPert Powder (PANalytical) or Bruker's X-ray diffraction tester.

[0120] Method: Fill the powder sample into the sample slot, flatten the upper surface with a glass sheet, and ensure that the upper surface of the sample is parallel to the edge of the slot. The scanning range is 2θ=10-90℃, and the total scanning time is not less than 5 minutes. After the scan is completed, open it with jade software, and automatically find the peak through Analysis→Find Peaks to identify the position of the (003) crystal plane diffraction peak and calculate the diffraction angle of the diffraction peak. The degree of structural recovery of the positive electrode material δ=θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first week of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first week of discharge.

[0121] (6) Testing method for particle size of positive electrode materials:

[0122] The volume particle size distribution range of the positive electrode material was measured by Malvern laser particle size analyzer to obtain D 90 , D 50 and D 10 .

[0123] (7) Testing method for specific surface area of ​​positive electrode material:

[0124] Equipment: Micromeritics Tristar 3020 surface area and pore size analyzer was used to test the surface area of ​​the positive electrode material.

[0125] Method: Weigh the mass of the empty sample tube m1; take 3g of sample and add it to the sample tube through a long-necked funnel; vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; the mass of the sample is m=m2-m1. The sample tube is placed in liquid nitrogen, and the nitrogen adsorption amount V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm. Among them, P / P0 is set to 0.05 / 0.1 / 0.15 / 0.20 / 0.25 / 0.30. Fit the isothermal adsorption curve, calculate the monolayer saturated adsorption amount Vm according to the slope and intercept, and then calculate the specific surface area according to Vm.

[0126] (8) Compacted density test of positive electrode materials:

[0127] The compaction density of the positive electrode material is tested using the American carver 4350, and the steps are as follows: weigh 1g of sample and put it into a mold and press it with a pressure of 3T for 30s. After pressing, the height is tested to calculate the compaction.

[0128] (9) SEM test of positive electrode materials:

[0129] Equipment: Hitachi S4800 scanning electron microscope, OXFORD Instrument's energy dispersive spectrometer.

[0130] SEM method: When testing powder samples, use tweezers or other tools to pick up the powder sample, spread it on the conductive glue and flatten it, and test it under 5kV / 10mA electron beam conditions. When testing cross-section samples, the material is coated on aluminum foil using conventional electrode preparation technology, then cut using a focused ion beam (FIB), and then tested under the same conditions as the powder sample under SEM.

[0131] (10) Electrochemical performance test:

[0132] After the positive electrode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, NMP (N-methylpyrrolidone) is added to make a uniform slurry, the slurry is evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it is rolled at a pressure of 10Mpa and cut into a circular pole piece with a diameter of 14mm. The negative electrode uses a Li metal sheet with a diameter of 14mm. The lithium-ion battery is assembled according to the CR2025 button battery in industry. The diaphragm is a Cellgard diaphragm, and the electrolyte uses an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte are assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5ppm.

[0133] Capacity test: The blue electric test system was used for electrical performance test (charge and discharge voltage was 3.0-4.3V, temperature condition was 25°C), 0.1C charge, 0.1C discharge, constant voltage cut-off current was 0.005C, and the discharge specific capacity mAh / g was calculated.

[0134] Cycle test: At 25°C and a charge / discharge voltage of 3.0-4.3V, charge and discharge at 0.5C / 1C for 50 cycles. The final capacity retention rate after 50 cycles is the cycle performance.

[0135] DC internal resistance (DCR) test: 0.1C charge and 0.1C discharge to 3.7V, after standing for 5h, place the battery at 25℃, then discharge at 2C for 30s, take a point every 0.1s, and calculate the average internal resistance of 30s as DCR (DC internal resistance).

[0136] Example 1

[0137] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo:nMn=0.6:0.1:0.3 to prepare a metal salt mixed solution. H2SO4 was then added into the mixed solution in an amount of 0.12% relative to the total molar amount of Ni / Co / Mn metals. The mixed solution was stirred ultrasonically for 2 h to ensure that the mixture was fully mixed to obtain a mixed solution.

[0138] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then the droplets are passed into a roasting furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C and the material stays in this temperature zone for 5 seconds; the temperature of the third temperature zone is 700°C and the residence time is 3 minutes. The volume concentration of oxygen in the roasting furnace is controlled at 15%. The chemical formula of the oxide precursor is Ni 0.60 Co 0.1 Mn 0.3 O 1.25 The precursor is crushed by air flow to a suitable particle size of D50=3.0μm and Dmax=15.

[0139] (3) The oxide precursor and Li2CO3 were mixed at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 1.05:1, placed in a Joule heat reactor, using an oxygen atmosphere, and the reaction pressure was controlled at 10Pa; the temperature was increased from room temperature to the first stage temperature of 500°C at a heating rate of 20°C / min, and kept warm for 4 hours; the temperature was increased to the second stage temperature of 700°C at a heating rate of 2°C / min, and kept warm for 6 hours; the temperature was decreased to the third stage temperature of 500°C at a cooling rate of 1°C / min, and kept warm for 4 hours; the temperature was increased to the fourth stage temperature of 900°C at a heating rate of 1°C / min, and kept warm for 2 hours; the temperature was decreased from the fourth stage temperature to room temperature at a cooling rate of 2°C / min, and the positive electrode material was obtained by air flow pulverization.

[0140] Example 2

[0141] The difference from Example 1 is:

[0142] The amount of H2SO4 added to the solution in step (1) is reduced to 0.015%.

[0143] Example 3

[0144] Different from Example 1,

[0145] In step (1), the amount of H2SO4 added to the solution is increased to 0.30%.

[0146] Example 4

[0147] Different from Example 1,

[0148] In step (2), the volume concentration of oxygen is controlled at 21%.

[0149] Example 5

[0150] The difference from Example 1 is:

[0151] In step (3), the specific steps of the primary sintering treatment are as follows: using an oxygen atmosphere and controlling the reaction gas pressure at 2 Pa; heating from room temperature to the first stage temperature of 600°C at a heating rate of 20°C / min, and keeping warm for 5 hours; heating to the second stage temperature of 1000°C at a heating rate of 0.5°C / min, and keeping warm for 12 hours; cooling to the third stage temperature of 700°C at a cooling rate of 0.5°C / min, and keeping warm for 6 hours; heating to the fourth stage temperature of 1000°C at a heating rate of 0.5°C / min, and keeping warm for 3 hours; cooling from the fourth stage temperature to room temperature at a cooling rate of 1°C / min, and obtaining the positive electrode material through air flow pulverization.

[0152] Example 6

[0153] The difference from Example 1 is:

[0154] In step (3), the specific steps of the primary sintering treatment are as follows: using an oxygen atmosphere and controlling the reaction gas pressure at 10 Pa; heating from room temperature to the first stage temperature of 300°C at a heating rate of 20°C / min, and keeping warm for 5 hours; heating to the second stage temperature of 900°C at a heating rate of 3°C / min, and keeping warm for 4 hours; cooling to the third stage temperature of 600°C at a cooling rate of 3°C / min, and keeping warm for 6 hours; heating to the fourth stage temperature of 700°C at a heating rate of 3°C / min, and keeping warm for 6 hours; cooling from the fourth stage temperature to room temperature at a cooling rate of 1°C / min, and obtaining the positive electrode material through air flow pulverization.

[0155] Example 7

[0156] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo:nMn=0.5:0.2:0.3 to prepare a metal salt mixed solution. H2SO4 was then added into the mixed solution in an amount of 0.12% relative to the total molar amount of Ni / Co / Mn metals. The mixed solution was stirred ultrasonically for 2 h to ensure that the mixture was fully mixed to obtain a mixed solution.

[0157] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C, and the material stays in this temperature zone for 3 seconds; the temperature of the third temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 15%. The chemical formula of the oxide precursor is Ni 0.5 Co 0.2 Mn 0.3 O1.2, the oxide precursor is crushed by air flow to a suitable particle size of D50=3.0μm, Dmax=15.

[0158] (3) The oxide precursor and Li2CO3 were mixed at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 1.05:1, placed in a Joule heat reactor, using an oxygen atmosphere, and the reaction pressure was controlled at 10Pa; the temperature was increased from room temperature to the first stage temperature of 500°C at a heating rate of 20°C / min, and kept warm for 4 hours; the temperature was increased to the second stage temperature of 800°C at a heating rate of 2°C / min, and kept warm for 6 hours; the temperature was decreased to the third stage temperature of 500°C at a cooling rate of 1°C / min, and kept warm for 4 hours; the temperature was increased to the fourth stage temperature of 1000°C at a heating rate of 1°C / min, and kept warm for 2 hours; the temperature was decreased from the fourth stage temperature to room temperature at a cooling rate of 2°C / min, and the positive electrode material was obtained by air flow pulverization.

[0159] Example 8

[0160] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo=0.98:0.01:0.01 to prepare a metal salt mixed solution. 0.12% H2SO4 was then added into the mixed solution and ultrasonically stirred for 2 h to fully mix the mixture to obtain a mixed solution.

[0161] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C, and the material stays in this temperature zone for 5 seconds; the temperature of the third temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 15%. The chemical formula of the oxide precursor is Ni 0.98 Co 0.01 Mn 0.01 O, the oxide precursor is crushed by air flow to a suitable particle size of D50=3.0μm, Dmax=15.

[0162] (3) Mix the oxide precursor and Li2CO3 at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 0.98:1, place in an atmosphere electric heating furnace or a Joule heat reactor, use an oxygen atmosphere, and control the reaction gas pressure at 10Pa; increase the temperature from room temperature to the first stage temperature of 500°C at a heating rate of 20°C / min, and keep it warm for 4 hours; increase the temperature from the second stage temperature of 700°C at a heating rate of 2°C / min, and keep it warm for 6 hours; decrease the temperature from the third stage temperature of 500°C at a cooling rate of 1°C / min, and keep it warm for 4 hours; increase the temperature from the fourth stage temperature of 700°C at a heating rate of 1°C / min, and keep it warm for 2 hours; decrease the temperature from the fourth stage temperature to room temperature at a cooling rate of 2°C / min, and obtain the positive electrode material through air flow pulverization.

[0163] Example 9

[0164] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo:nMn=0.8:0.1:0.1 to prepare a metal salt mixed solution. H2SO4 was then added into the mixed solution in an amount of 0.12% relative to the total molar amount of Ni / Co / Mn metals. The mixed solution was stirred ultrasonically for 2 h to ensure that the mixture was fully mixed to obtain a mixed solution.

[0165] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C, and the material stays in this temperature zone for 3 seconds; the temperature of the third temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 15%. The chemical formula of the oxide precursor is Ni 0.8 Co 0.1 Mn 0.1 O1.1, the oxide precursor is crushed by air flow to a suitable particle size of D50=3.0μm, Dmax=15.

[0166] (3) Mix the oxide precursor and LiOH in a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 1.1:1, place in an atmosphere electric heating furnace or a Joule heat reactor, use an oxygen atmosphere, and control the reaction gas pressure at 10 Pa; increase the temperature from room temperature to the first stage temperature of 500°C at a heating rate of 20°C / min, and keep it warm for 4 hours; increase the temperature from the second stage temperature of 750°C at a heating rate of 2°C / min, and keep it warm for 6 hours; decrease the temperature from the third stage temperature of 550°C at a cooling rate of 1°C / min, and keep it warm for 4 hours; increase the temperature from the fourth stage temperature of 850°C at a heating rate of 1°C / min, and keep it warm for 2 hours; decrease the temperature from the fourth stage temperature to room temperature at a cooling rate of 2°C / min, and obtain the positive electrode material through air flow pulverization.

[0167] Example 10

[0168] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo=0.70:0.10:0.20 to prepare a metal salt mixed solution. H2SO4 was then added into the mixed solution in an amount of 0.12% relative to the total molar amount of Ni / Co / Mn metals. The mixed solution was stirred ultrasonically for 2 h to ensure that the mixture was fully mixed to obtain a mixed solution.

[0169] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C, and the material stays in this temperature zone for 3 seconds; the temperature of the third temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 15%. The chemical formula of the oxide precursor is Ni 0.7 Co 0.1 Mn 0.2 O, the oxide precursor is crushed by air flow to a suitable particle size of D50=3.0μm, Dmax=15.

[0170] (3) Mix the oxide precursor and Li2CO3 at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 0.98:1, place in an atmosphere electric heating furnace or a Joule heat reactor, use an oxygen atmosphere, and control the reaction pressure at 10Pa; increase the temperature from room temperature to the first stage temperature of 500°C at a heating rate of 20°C / min, and keep it warm for 4 hours; increase the temperature from the second stage temperature of 700°C at a heating rate of 2°C / min, and keep it warm for 6 hours; decrease the temperature from the third stage temperature of 500°C at a cooling rate of 1°C / min, and keep it warm for 4 hours; increase the temperature from the fourth stage temperature of 880°C at a heating rate of 1°C / min, and keep it warm for 2 hours; decrease the temperature from the fourth stage temperature to room temperature at a cooling rate of 2°C / min, and obtain the positive electrode material through air flow pulverization.

[0171] Embodiment 11

[0172] The difference from Example 1 is:

[0173] (1) Nickel nitrate, cobalt nitrate, manganese nitrate and zirconium nitrate were weighed and added into water in a molar ratio of nNi:nCo:nMn:nZr=0.6:0.1:0.3:0.005 to prepare a metal salt mixed solution. H2SO4 was then added into the mixed solution in an amount of 0.12 wt% relative to the total molar amount of Ni / Co / Mn / Zr metals. The mixed solution was stirred ultrasonically for 2 h to ensure thorough mixing to obtain a mixed solution.

[0174] The other steps are the same as in Example 1.

[0175] Example 12

[0176] The difference from Example 1 is:

[0177] The airflow pulverized product prepared in step (3) was mixed with alumina at a mass ratio of 99:1, placed in a Joule heat reactor, and heated from room temperature to 450°C at a heating rate of 20°C / min using an air atmosphere, and kept at that temperature for 8 hours. The temperature was then cooled to room temperature at a rate of 2°C / min to obtain a positive electrode material.

[0178] Embodiment 13

[0179] The difference from Example 9 is:

[0180] In step (1), nickel nitrate, cobalt nitrate and aluminum nitrate are weighed in a molar ratio of nNi:nCo:nAl=0.8:0.1:0.1 and added to water to prepare a metal salt mixed solution, and then 0.12% H2SO4 relative to the total molar amount of Ni / Co / Al metal is added to the mixed solution, and ultrasonic stirring is performed for 2 hours to fully mix and obtain a mixed solution.

[0181] In step (3), the temperature of the fourth stage is set to 870°C.

[0182] Embodiment 14

[0183] Different from Example 1,

[0184] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo:nMn=0.6:0.1:0.3 to prepare a metal salt mixed solution. 0.6% H2SO4 was then added into the mixed solution and ultrasonically stirred for 2 h to fully mix the mixture to obtain a mixed solution.

[0185] Comparative Example 1

[0186] Different from Example 1,

[0187] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 15%. The chemical formula of the oxide precursor is Ni 0.60 Co 0.1 Mn 0.3 O, the precursor is crushed by air flow to a suitable particle size of D50 = 3.0 μm, Dmax = 15.

[0188] Comparative Example 2

[0189] Different from Example 1,

[0190] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C, and the material stays in this temperature zone for 3 seconds; the temperature of the third temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 30%. The chemical formula of the oxide precursor is Ni0.60 Co 0.1 Mn 0.3 O, the oxide precursor is crushed by air flow to a suitable particle size of D50=3.0μm, Dmax=15.

[0191] Comparative Example 3

[0192] Different from Example 1,

[0193] (3) The oxide precursor and Li2CO3 are mixed at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 1.05:1, and placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere, and the reaction gas pressure is controlled at 2Pa; the temperature is increased from room temperature to the first stage temperature of 600°C at a heating rate of 20°C / min, and kept warm for 5 hours; the temperature is increased to the second stage temperature of 1000°C at a heating rate of 0.2°C / min, and kept warm for 12 hours; the temperature is decreased to the third stage temperature of 700°C at a cooling rate of 0.2°C / min, and kept warm for 6 hours; the temperature is increased to the fourth stage temperature of 1000°C at a heating rate of 0.2°C / min, and kept warm for 3 hours; the temperature is decreased from the fourth stage temperature to room temperature at a cooling rate of 1°C / min, and the proportion of small particles below 1 μm in the positive electrode material is 4.2% after air flow crushing.

[0194] Comparative Example 4

[0195] Different from Example 1,

[0196] (3) Mix the oxide precursor and Li2CO3 at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 1.05:1, place in an atmosphere electric heating furnace or a Joule heat reactor, use an oxygen atmosphere, and control the reaction gas pressure at 10Pa; increase the temperature from room temperature to the first stage temperature of 900°C at a heating rate of 20°C / min, and keep it warm for 8h; increase the temperature to the second stage temperature of 700°C at a heating rate of 3°C / min, and keep it warm for 2h; cool to room temperature at a cooling rate of 3°C / min, and after air flow pulverization, the proportion of small particles below 1μm in the positive electrode material is 20%.

[0197] Comparative Example 5

[0198] (1) Nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water in a molar ratio of nNi:nCo:nMn=0.6:0.1:0.3 to prepare a metal salt mixed solution. H2SO4 was then added into the mixed solution in an amount of 0.6% relative to the total molar amount of Ni / Co / Mn metals. The mixed solution was stirred ultrasonically for 2 h to ensure that the mixture was fully mixed to obtain a mixed solution.

[0199] (2) The mixed solution is atomized by a plasma rotating electrode to form micronized droplets of about 20 μm in size, and then enters a calcining furnace for thermal decomposition to prepare an oxide precursor. The temperature of the first temperature zone is 400°C, and the residence time is 60 seconds; the temperature of the second temperature zone is 1100°C, and the material stays in this temperature zone for 3 seconds; the temperature of the third temperature zone is 700°C, and the residence time is 3 minutes. The volume concentration of oxygen in the calcining furnace is controlled at 30%. The chemical formula of the oxide precursor is Ni 0.60 Co 0.1 Mn 0.3 O, the oxide precursor is crushed by air flow to a suitable particle size of D50=3.0μm, Dmax=15.

[0200] (3) Mix the oxide precursor and Li2CO3 at a molar ratio of Li / Me (Me is the sum of Ni, Co, and Mn) of 1.05:1, place in an atmosphere electric heating furnace or a Joule heat reactor, use an oxygen atmosphere, and control the reaction gas pressure at 10Pa; increase the temperature from room temperature to the first stage temperature of 900°C at a heating rate of 20°C / min, and keep it warm for 8h; increase the temperature to the second stage temperature of 700°C at a heating rate of 3°C / min, and keep it warm for 2h; cool to room temperature at a cooling rate of 3°C / min, and after air flow pulverization, the proportion of small particles below 1μm in the positive electrode material is 20%.

[0201] The positive electrode materials of the above embodiments (abbreviated as S1 to S14) and comparative examples (abbreviated as D1 to D5) were subjected to physical and chemical performance tests and electrochemical tests. The test results are shown in Tables 1 and 2 below.

[0202] Table 1 Comparison of positive electrode materials of the embodiment and the comparative example

[0203]

[0204]

[0205] Table 2 Electrochemical performance test results of positive electrode materials of the embodiments and comparative examples

[0206]

[0207] The present application controls the proportion of particles with a particle size of less than 1 μm in the positive electrode material on the basis of controlling the enrichment of sulfur element in the positive electrode material to ≤70%. The doping of sulfur atoms can improve the lattice rotation of the positive electrode material and enhance the structural stability of the positive electrode material. Controlling the proportion of particles with a particle size of less than 1 μm can reduce the side reaction between the positive electrode material and the electrolyte and improve the cycle performance of the positive electrode material. Under the synergistic effect of the two, the positive electrode material can have excellent structural stability and long cycle performance.

[0208] Compared with Example 1, since the temperature in the second temperature zone is lower, most of the sulfate ions in the mixed solution are enriched on the surface of the oxide precursor and are difficult to enter the interior of the oxide precursor, resulting in a significant increase in β, a decrease in the cycle stability of the positive electrode material, which is not conducive to the transmission of lithium ions and an increase in internal resistance.

[0209] Compared with Example 1, in Comparative Example 2, due to the excessively high oxygen concentration during the thermal decomposition process, it is difficult for sulfate ions in the mixed solution to replace oxygen in the crystal lattice, resulting in a significant increase in β, a decrease in the cycle stability of the positive electrode material, which is not conducive to the transmission of lithium ions and an increase in internal resistance.

[0210] Compared with Example 1, since the number of particles of the positive electrode material with a particle size of less than 1 μm accounts for too small a proportion, the transmission path of lithium ions increases, the initial DCR of the positive electrode material increases, and the compaction density of the positive electrode material decreases.

[0211] Compared with Example 1, since the number of particles of the positive electrode material with a particle size of less than 1 μm accounts for too large a proportion, the side reaction between the positive electrode material and the electrolyte is aggravated, and the cycle stability of the positive electrode material is reduced.

[0212] In Comparative Example 5, compared with Example 1, too much dilute sulfuric acid is added to the mixed solution. Excessive sulfur element will also inhibit the growth of primary particles, the number of particles with a particle size of less than 1 μm in the positive electrode material increases, the side reaction between the positive electrode material and the electrolyte is aggravated, the β of the positive electrode material is greatly increased, the initial DCR of the positive electrode material is increased, and the cycle stability of the positive electrode material is greatly reduced.

[0213] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A positive electrode material, characterized in that: The surface enrichment of sulfur element in the positive electrode material is β=A2 / A1, β%≤70%, A1 is the total mass content of sulfur element in the positive electrode material, and A2 is the mass content of sulfur element in free sulfate ions of the positive electrode material; in the scanning electron microscope image (SEM) of the positive electrode material, the number of particles with a particle size less than 1 μm in the positive electrode material accounts for 6% to 18%.

2. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Li x Ni a Co b N c M1 d O2, wherein 0.98≤x≤1.1, 0.5≤a≤0.98, 0<b≤0.2, 0<c≤0.30, 0≤d≤0.1, a+b+c+d=1, the N element includes at least one of Mn and Al, and the M1 element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.

3. The positive electrode material according to claim 1, characterized in that The total mass content A1 of sulfur in the positive electrode material satisfies 50ppm≤A1≤1000ppm; and / or, the mass content A2 of sulfur in the surface free sulfate groups in the positive electrode material satisfies 0ppm<A2≤700ppm; and / or, 40%≤β≤50%.

4. The positive electrode material according to claim 1, characterized in that The positive electrode material includes primary particles and a coating layer located on at least a portion of the surface of the primary particles, the coating layer includes element M2, and the element M2 includes at least one of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co and Mn.

5. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal positive electrode material.

6. The positive electrode material according to any one of claims 1 to 5, characterized in that The volume median particle size of the positive electrode material is 1.5 μm to 5.0 μm.

7. The positive electrode material according to any one of claims 1 to 5, characterized in that The specific surface area of ​​the positive electrode material is 0.5 m 2 / g~1.2m 2 / g.

8. The positive electrode material according to any one of claims 1 to 5, characterized in that The compaction density of the positive electrode material is 3.0 g / cm 3 ~3.3g / cm 3 .

9. The positive electrode material according to any one of claims 1 to 5, characterized in that During the first cycle of charge and discharge, the structural recovery degree δ of the positive electrode material satisfies: 99.7%≤δ≤100.0%; wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first cycle of discharge.

10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Positive electrode material, positive electrode sheet, and battery

    WO2026138118A1